The Real Estate Transfer Tax and Government Ideology: Evidence from the German States - Manuela Krause; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Since 2007 the German state governments have been allowed by a constitutional reform to set real estate transfer tax rates. We exploit this reform and investigate whether government ideology predicts the levels and increases in the real estate transfer tax rates. The results show that leftwing and center governments were more active in increasing the real estate transfer tax rates than rightwing governments. Many voters were disenchanted with the policies and platforms of the established German parties. Disenchantment notwithstanding, real estate transfer tax policies show that the established political parties are still prepared to offer polarized policies.
Keywords: D72; H20; H71; P16; R38; 330; Real estate transfer tax; partisan politics; reform; government ideology; fiscal federalism